Determining operational capabilities in halal food manufacturing industry - Tamam, Mohamad Norjayadi; Abdurahman, Abang Zainoren Abang; Abdullah, Firdaus (2017)
Purpose - The scope of the study is on Sarawak Halal food manufacturing firms performance in relations to operational capabilities dimensions. This preliminary research paper aims to establish the dimensions of Halal operational capabilities and process management as an intervening variable in Halal food manufacturing industry in Sarawak, Malaysia.The objective is to determine the dimensions of Operational Capabilities affecting Halal food manufacturing firm performance.Earlier operational capabilities studies by Skinner (1969) suggested that manufacturing offered an organization certain capabilities that could be used as competitive weapons.Operational capabilities as a competitive advantage factors is in tandem with resource-based view (RBV) of the firm, which has emerged as a theoretical framework for analysing the sources and sustainability of competitive success (Barney, 1991 and Grant 1991). Several dimensions of capability (cost, quality and time) have been identified by Skinner (1974) as crucial to an organizations longterm success. Based on focus group discussion output, Halal operational capabilities dimensions covers improvement, innovation, cooperation, customization, responsiveness and reconfiguration. Further study required to identify which capabilities are more important than others that influence the Halal firms performance.Methodology - This exploratory research paper is based on focus group discussion held in Sarawak, Malaysia to define the scope of Halal Operational Capabilities.The focus group has been structured to allow open, in-depth discussions with a group of selected individuals led by the researcher, to explore the dimensions of Halal operational capabilities (Walden, 2006).Focus groups were conducted within the class room setting at Malaysia Productivity Corporation (MPC) Sarawak in February 2017. The session were audiotaped, and tapes are transcribed verbatim to ensure systematic analysis of the discussions. Discussions duration is approximately 3.5 hours and were facilitated by a moderator and co-moderator.The focus group assessed whether the dimensions of operational capabilities in Halal industry reflected the perceptions of representatives from the companies which consist of supervisory and managerial position and above. The focus group discussion is aiming at identify the competitive advantage factor specifically from operational capabilities perspectives among the Halal industry player.